CLIENT SERVER SYSTEMS APPLICATIONS USING MICROSOFT ACCESS AND MICROSOFT VB 6.0 - Heri Setyono; Drs. Soenarto Usna, MMSI (Jurnal Sistem Informasi, 2006)
This writing explains the application on the client and the server bagiman connectionof the two different applications. This application uses Microsoft Access database andalso serves as a program on the server. In the field of administration, the authors alsoprovide a statement of transactions per user and per day. With this database theauthors try to create applications that can be changed according to the parameterexisting in the database so that the application form which can be replaced asnecessary.